The Impact of Tigecycline on Fibrinogen Level post Cytoreductive Surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) Patients. A Randomized Controlled Study. (4th October 2017) - Al Duhailib, Zainab; Hakeam, Hakeam; Salahuddin, Nawal; Amin, Tarek
Abstract: Background: Tigecycline (TIG), a new broad spectrum antibiotic and effective antimicrobial option for various surgical infectious complications including wound and intraabdominal infections. Coagulopathy and hypofibrinogenemia have been recently reported in different patient population receiving tigecycline. Objective: To compare the effect of TIG use on fibrinogen (FIB) level, prothrombin time (PT) and activated partial thromboplastin time (aPTT) vs. imipenem/cilastatin (IMI), in patients undergoing cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) with postoperative infection. Methods: Prospective, randomized, open label study conducted at King Faisal Specialist Hospital and Research Centre, Saudi Arabia. Patients underwent CRS and HIPEC and required empirical antibiotics were randomly allocated to two groups. Group 1 received TIG plus ceftazidime or aztreonam, while group 2 received IMI monotherapy. FIB, PT, aPTT were assessed at baseline then on day 0, 1, 3, 5, 8 postoperatively then after 48 hours of stopping antibiotics. Results: Twenty patients received TIG, while 22 patients received IMI. Baseline demographics and coagulation indices were comparable in both groups. The amounts of blood products transfused intra- and post-operatively were not different between the two groups. The mean FIB levels was significantly lower in TIG group compared with IMI group on day 3 (4.1 ± 1.2 vs.. 5.9 ± 1.3 g/L; P < 0.001), day 5 (3.8 ± 1.2 vs. 6.6 ± 1.1 g/L; P < 0.001), day 8 (3.5 ± 1.3 vs. 5.8 ± 1.6 g/L; P = 0.001) and after 48 hours of antibiotics stop (4.11 ± 1.4 vs. 6.1 ± 1.2 g/L; P = 0.025). Two patients in each group developed hypofibrinogenemia (10% in TIG and 9% in IMI; P = 0.73). The mean PT was significantly prolonged in TIG group compared with IMI group on day 3 postoperatively (16.4 ± 1.5 vs 15.5 ± 1.3 seconds; P = 0.045), while the aPTT means were significantly prolonged on the following days postoperatively: 5 (41 ± 9 vs. 36.2 ± 3 seconds; P = 0.02) and 8 (39.4 ± 5.5 vs. 34.5 ± 3.7 seconds; P = 0.004) for TIG and IMI groups respectively. The rate of bleeding was comparable on both groups of the study (20% vs.. 9%; P = 0.31). Conclusion: TIG demonstrated significant alterations on fibrinogen and coagulation indices in patients undergoing major surgery. Disclosures: All authors: No reported disclosures.